Genotypic and antimicrobial resistance characterizations of Cronobacter sakazakii isolated from powdered milk infant formula: A comparison between domestic and imported products. Issue 12 (30th October 2020) - Pakbin, Babak; Mahmoudi, Razzagh; Mousavi, Shaghayegh; Allahyari, Samaneh; Amani, Zahra; Peymani, Amir; Qajarbeygi, Peyman; Hoseinabadi, Zahra
Abstract: Cronobacter sakazakii, an opportunistic foodborne pathogen and a main cause of meningitis in neonates, is usually isolated from powdered milk infant formula (PMIF). At the present study, C. sakazakii were isolated from imported and domestically produced PMIF samples and identified by detection of ompA gene using real‐time PCR SYBR green melting curve following the evaluation of antimicrobial susceptibility and genotyping of the isolates employing BOX‐PCR and RAPD methods. We detected totally 5% contamination rate and a significantly higher prevalence of C. sakazakii in bulky imported domestically packaged PMIF samples. Also, our isolates were recognized as multidrug‐resistant pathogen completely resistant to ampicillin and amoxicillin; and intermediately resistant to ciprofloxacin and tetracycline antimicrobials. Genotype clustering patterns of bulky imported and imported product isolates were identical by both genotyping methods. Far genetic relatedness of domestic isolate to other isolates and the reference strain indicated higher genetic diversity of the domestic isolate genome. Multidrug resistance and diverse population genetic make complicated situation for determination of strategies for infectious disease prevention. Abstract : Cronobacter sakazakii strains were isolated from imported and domestically produced PMIF samples and identified by detection of ompA genes using real‐time PCR SYBR green melting curve following the evaluation of antimicrobial susceptibility and genotyping of the isolates employing BOX‐PCR and RAPD methods. A close relationship between genotype clustering and antimicrobial susceptibility patterns showed that drug resistance properties of C. sakazakii isolates affect genetic diversity and genomic evolution.